\(x^2=\sqrt{2008y}-2007\)

...">

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 9 2017

Ta có:\(\left(\sqrt[]{x^2+2007}+x^{ }\right)\left(\sqrt{x^2+2007}-x\right)\left(\sqrt{y^2+2007}+y\right)\left(\sqrt{y^2+2007}-y\right)=2007\left(\sqrt{x^2+2007}-x\right)\left(\sqrt{y^2+2007}-y\right)\)

\(\Rightarrow2007^2=2007\left(\sqrt{x^2+2007}-x\right)\left(\sqrt{y^2+2007}-y\right)\)

\(\Rightarrow\left(\sqrt{x^2+2007}-x\right)\left(\sqrt{y^2+2007}-y\right)=2007\)

\(\Rightarrow xy-x\sqrt{y^2+2007}-y\sqrt{x^2+2007}+\sqrt{\left(x^2+2007\right)\left(y^2+2007\right)}=2007\)(1)

\(\left(\sqrt[]{x^2+2007}+x^{ }\right)\left(\sqrt{y^2+2007}+y\right)=xy+x\sqrt{y^2+2007}+y\sqrt{x^2+2007}+\sqrt{\left(x^2+2007\right)\left(y^2+2007\right)}=2007\)(2)

cộng (1) và (2)

\(\Rightarrow xy+\sqrt{\left(x^2+2007\right)\left(y^2+2007\right)}=2007\)

\(\Leftrightarrow\sqrt{\left(x^2+2007\right)\left(y^2+2007\right)}=2007-xy\)

\(\Rightarrow x^2y^2+2007\left(x^2+y^2\right)+2007^2=2007^2-2.2007xy+x^2y^2\)

\(\Rightarrow x^2+y^2=-2xy\Rightarrow\left(x+y\right)^2=0\Rightarrow M=0\)

29 tháng 9 2017

thank you Bertram Đức Anh